Grain Size and Depositional Pattern of Sediment from Okeluse Area, Southwestern Nigeria (Global Journal of Science Frontier Research, 2014)
Grain size and depositional pattern of sediment from Okeluse area, Southwestern Nigeria have been carried to evaluate its textural parameters and statistical measures to depict the depositional pattern of sediments in the study area. A total of ten samples were collected for this study. The method of sampling adopted for this study is a spot sampling method. The samples were processed and sieved following international standards. Statistical parameters studied include. The graphic mean values (M z ) ranges from 1.333 -2.267. The inclusive graphic skewness (sk 1 ) of grain analysis data show that they are negatively skewed and implies that the sediments are strongly coarsely, coarsely and nearly symmetrical skewed. Sediments in OKL 1 , OKL 2 and OKL 10 are strongly coarsely skewed, while OKL 3 , OKL 4 , OKL 5 , OKL 6 , OKL 8 and OKL 9 are coarsely skewed. OKL 7 is nearly symmetrical skewed. The sorting kurtosis of the sediments shows that they are either leptokurtic or very platykurtic. OKL 3 , OKL 5 and OKL 7 are very platykurtic, while OKL 1 , OKL 2 , OKL 4 , OKL 6 , OKL 8 , OKL 9 and OKL 10 are leptokurtic. The grain size distribution reveals that the transporting medium must have undergone series of rise and fall in its velocity. In the present study, all the ten samples analyzed shows the dominance of saltation and suspension domains of size-population.
Keywords: grain-size; deposition; sediment; okeluse